Pharmacoepidemiological Effects of Antibacterial Drugs for Community-Acquired Pneumonia in Children of Different Ages in a Modern Interpretation - Kodirova Shakhlo Salokhitdinovna (Journal of Science in Medicine and Life, 2025)
The article presents the main goals of antibiotic therapy and its indications in acute respiratory viral infections. Literature data on the modern spectrum of pathogens of bacterial foci of the lower respiratory tract (bacterial bronchitis and pneumonia) in children are presented. The spectrum and mechanisms of antibiotic resistance of isolated pathogens are listed. A brief overview of the pharmacological properties and sensitivity of antibacterial drugs of the main groups recommended for the treatment of lower respiratory tract diseases in children is given - semi-synthetic aminopenicillins, drugs protected by inhibitors, cephalosporins, macrolides. Local algorithms of antibacterial therapy for bronchitis and pneumonia are presented, which are based on the principles of evidence-based medicine. The advantages of the soluble oral form of antibacterial drugs - Solutab dispersible tablets, which have high bioavailability, efficacy and safety, are named.